The Influence of Capital Structure and Idiosyncratic Risk on Company Value With Industri Type As Moderating on Energy Company Listed on The Indonesia Stock Exchange for The Period 2016-2020 - Suyono, Suyono; Amin, Muhammad Nuryatno (Asosiasi Dosen Akuntansi Indonesia, 2022)
The purpose of this study is to test and prove empirically the effect of capital structure and idiosyncratic risk, type of industry on the value of the Indonesian stock exchange sector. In addition, the purpose of this study is to empirically test and prove the type of industry to strengthen the effect of capital structure on the value of the Indonesian stock exchange sector. This last study aims to test and prove empirically the type of industry strengthens the effect of idiosyncratic risk on the value of the Indonesian Stock Exchange sector. The population in this study are energy sector companies listed on the Indonesia Stock Exchange for 74 years 2016-2020. The sampling technique used purposive sampling method. Based on this technique, the number of samples used in this study were 53 companies. The data analysis technique used in this study is multiple linear regression analysis with a moderating effect. The results of this study indicate that capital structure and idiosyncratic risk are not significant to the value of companies in the Indonesian stock exchange sector. The type of industry has a significant positive effect on the value of companies in the Indonesian stock exchange sector. The variable type of industry strengthens the positive influence of capital structure and idiosyncratic risk on the value of companies in the Indonesian stock exchange sector. For the control variable, ROA is not significant to firm value, while for CR it is significant positive to firm value. The variable value of the firm is influenced by variables of Capital Structure, idiosyncratic risk, Type of Industry, Profitability, and Liquidity of 9.6%. Meanwhile, 90.4% was influenced by other variables that were not included in this research model.